2022
DOI: 10.1101/2022.06.09.22276196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated waning of the humoral response to SARS-CoV-2 vaccines in obesity

Abstract: Obesity is associated with an increased risk of severe Covid-19. However, the effectiveness of SARS-CoV-2 vaccines in people with obesity is unknown. Here we studied the relationship between body mass index (BMI), hospitalization and mortality due to Covid-19 amongst 3.5 million people in Scotland. Vaccinated people with severe obesity (BMI>40 kg/m2) were significantly more likely to experience hospitalization or death from Covid-19. Excess risk increased with time since vaccination. To investigate the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
3
8
1
Order By: Relevance
“…However, adequate glycaemic control after vaccination improved immunological responses and may even restore the protection against SARS-CoV-2 infection 31. We did not find an association between peak antibody levels with BMI, but a study in Scotland suggested that obesity could lead to faster waning of immunity after vaccination, which may explain increased disease severity from breakthrough infections in people with obesity 32. Previous studies also found that hypertension33 and smoking34 35 were associated with lower antibody responses post-vaccination; there was marginal evidence for a similar effect in our population (p=0.09; 0.12).…”
Section: Discussioncontrasting
confidence: 55%
“…However, adequate glycaemic control after vaccination improved immunological responses and may even restore the protection against SARS-CoV-2 infection 31. We did not find an association between peak antibody levels with BMI, but a study in Scotland suggested that obesity could lead to faster waning of immunity after vaccination, which may explain increased disease severity from breakthrough infections in people with obesity 32. Previous studies also found that hypertension33 and smoking34 35 were associated with lower antibody responses post-vaccination; there was marginal evidence for a similar effect in our population (p=0.09; 0.12).…”
Section: Discussioncontrasting
confidence: 55%
“…The SARS-CoV-2 virus used in this study was the wildtype (lineage B) isolate SARS-CoV-2/human/Liverpool/REMRQ0001/2020, a kind gift from Ian Goodfellow (University of Cambridge, UK), isolated by Lance Turtle (University of Liverpool, UK) and David Matthews and Andrew Davidson (University of Bristol, UK) 92,93 ( Plasma was heat-inactivated at 56°C for 30 mins before use, and neutralizing antibody titers at 50% inhibition (NT50) measured as previously described. [94][95][96] In brief, luminescent HEK293T-ACE2-30F-PLP2 reporter cells (clone B7) expressing SARS-CoV-2 Papain-like protease-activatable circularly permuted firefly luciferase (FFluc) were seeded in flat-bottomed 96-well plates. The next day, SARS-…”
Section: Live Neutralizationmentioning
confidence: 99%
“…The SARS-CoV-2 virus used in this study was the wildtype (lineage B) isolate SARS-CoV-2/human/Liverpool/REMRQ0001/2020, a kind gift from Ian Goodfellow (University of Cambridge), isolated by Lance Turtle (University of Liverpool) and David Matthews and Andrew Davidson (University of Bristol) (Daly et al, 2020; Patterson et al, 2020)(Plasma was heat-inactivated at 56°C for 30 mins before use, and neutralizing antibody titres at 50% inhibition (NT 50 ) measured as previously described (Bergamaschi et al, 2021; Gerber et al, 2022; van der Klaauw et al, 2022). In brief, luminescent HEK293T-ACE2-30F-PLP2 reporter cells (clone B7) expressing SARS-CoV-2 Papain-like protease-activatable circularly permuted firefly luciferase (FFluc) were seeded in flat-bottomed 96-well plates.…”
Section: Methodsmentioning
confidence: 99%